1992
DOI: 10.1210/jc.75.2.424
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the insulin-like growth factor-II/mannose-6-phosphate receptor in multiple human tissues during fetal life and early infancy

Abstract: The insulin like growth factor-II/mannose-6-phosphate (IGF-II/ M6P) receptor has been detected in many cells and tissues. In the rat, there is a dramatic developmental regulation of IGF-II/MGP receptor expression, the receptor being high in fetal and neonatal tissues and declining thereafter. We have systematically studied the expression of the human IGF-II/MGP receptor protein in tissues from 10 human fetuses and infants (age 23 weeks gestation to 24 months postnatal). We have asked 1) whether there is differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 2 publications
(3 reference statements)
2
41
0
1
Order By: Relevance
“…50-60 % in the younger cohort. The increase in resistance to treatment in the older animals may be related to the reported decline in the density of cell surface CI-MPR with age [25,26]. It has also been suggested that the structure of the stored glycogen and the intracellular trafficking and lysosomal processing of the exogenous enzyme may be altered in aged Pompe cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…50-60 % in the younger cohort. The increase in resistance to treatment in the older animals may be related to the reported decline in the density of cell surface CI-MPR with age [25,26]. It has also been suggested that the structure of the stored glycogen and the intracellular trafficking and lysosomal processing of the exogenous enzyme may be altered in aged Pompe cells.…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscles also purportedly have a lower abundance of the CI-MPR (cationindependent M6P receptor, where M6P stands for mannose 6-phosphate) that is essential for cellular uptake of the lysosomal enzyme [2,25,26]. Furthermore, CHO cell-and transgenic animalderived rhGAA appear to have less optimal affinity for the CI-MPR.…”
Section: Introductionmentioning
confidence: 99%
“…No difference was seen between the PBS versus AAV-treated NHPs [two-way repeated-measures ANOVA, p > 0.37, F(35,35) = 1.11]. (Funk et al, 1992;Ghosh et al, 2003). Intravenous administration of recombinant ARSA in the MLD mouse model reduced sulfatide storage in the brain and peripheral nerves, but was efficacious only when injected into young mice (Matzner et al, 2005;Matthes et al, 2012).…”
Section: Approaches To Therapy Of Mldmentioning
confidence: 99%
“…Because the vector was administered in multiple loci in this study, it was not possible to determine whether the enzyme spread was due to retrograde axonal transport of the vector or to uptake through the M6P receptor system, or occurred by an unknown mechanism (Funk et al, 1992;Ghosh et al, 2003;Kells et al, 2012). Because this was not a formal safety and toxicology study, determination of the biodistribution of the AAVrh.10 vector in the brain and visceral organs was not performed in this study; instead we focused on the efficacy-related distribution of the transgene end-product, ARSA enzyme, to specify potential therapeutic coverage across the brain as a comparison for the various routes of administration.…”
Section: Aav Vector Direct Cns Therapy Of Mldmentioning
confidence: 99%
See 1 more Smart Citation